Argentine agricultural policy: Producer and consumer support estimates 2007-2012 - Marcos Gallacher; Daniel Lema (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2014)
This paper analyzes agricultural policy in Argentina and calculates the degree of support received by producers and consumers. We present a summary of developments in the agricultural policy environment that have occurred in the last decades in Argentina, as well as the resulting performance of the agricultural sector. The concepts of Producer Support Estimates, Consumer Support Estimates, General Services Support Estimates, Producer Nominal Assistance Coefficient and Nominal Protection Coefficient are used to analyse different dimensions of transfers occurring between agricultural producers, consumers and taxpayers in the period 2007-2012. Total transfers from producers have averaged US 11.000 million annually or 26% of total gross farm receipts. Support flowing from the public sector to producers in the form of R&D, infrastructure and other "public good" type of inputs totalize some 500 million annually.
Keywords: Q18; Q11; 330; Agricultural Policy; Agricultural Prices; Producer Support Estimates